Using a Case Scenario-Based Self-Teaching Module to Increase Overall Skill in ECG Interpretation for Pediatric Residents - Jacqui Weinberg; Mary Ottolini; Jeffrey Sestokas; E. Anne Greene (Association of American Medical Colleges, 2013)
Abstract Introduction There is general agreement in the literature that standard lecture-based teaching in interpretation of ECGs in both adult and pediatric training programs is ineffective. Computer based modules have been used as part of Emergency Medicine training programs but there are very few self-directed learning resources available for pediatric ECG interpretation. Pediatric ECGs are especially challenging to interpret because of the age associated developmental changes which do not exist in the adult population, and pattern recognition is more complicated in pediatrics. We therefore perceived a need to develop, implement, and evaluate a novel training tool for pediatric residents to improve their ECG interpretation. Methods This case-based, self-study resource for pediatric ECG interpretation and arrhythmia recognition contains 11 cases which cover a broad range of basic ECG principles, as well as more critical arrhythmias and clinical presentations. Each ECG is imbedded in a clinical context and all the incorrect answers are explained with examples. Normal ECG findings for each age are shown. Clinical scenarios are designed to be the classic presentation for a given ECG such as supraventricular tachycardia in an infant, long QTc in a near drowning patient, and chest pain during exercise in a patient with hypertrophic cardiomyopathy. Critical rhythms such as complete heart block and ventricular tachycardia are shown, as are normal variations such as early repolarization. The module was tested for a year with pediatric residents and modified to provide clarity in the cases. The module was used for selfstudy followed by a small-group debriefing session after 2-3 weeks of independent use by the residents. Results Ninety-five percent of the residents on rotation for the study period completed the pre- and posttest for the learning module. The mean pretest correct percentage was 53%. The average posttest correct score for all questions was 81%, a significant difference as per a two-tailed t test (p = .01). The mean pretest confidence level was 2.95 across all questions (1 = not confident, 4 = very confident) increasing to 3.43 across all questions at posttest. This was a significant difference as determined by the Wilcoxen Rank Test (p = .003). Discussion ECG interpretation is an intricate skill not easily conveyed in a lecture format. Providing effective instruction for the more intricate interpretation of ECGs in the pediatric setting is even more difficult. We therefore perceived a need to develop, implement and evaluate a novel training tool, which has helped pediatric residents improve their ECG interpretation.